2019
DOI: 10.31235/osf.io/eh5bg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of public surveillance cameras on crime clearance rates

Abstract: Much research has examined the crime reduction benefits of public close-circuit television (CCTV) cameras, suggesting that cameras may not deter enough crime to justify their cost. Another benefit of CCTV though is its utility in investigations and in clearing cases, which has been much less studied. Using a sample of public crimes and case clearances in Dallas, Texas, we examine the efficacy that public CCTV cameras increase case clearance rates using a pre-post research design. We find that cases closer to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
1
6
0
1
Order By: Relevance
“…Coupe and Kaur (2005) similarly found that clearance for burglary was significantly higher when the crime took place at a CCTV monitored location. Jung and Wheeler (2019) similarly showed that the introduction of CCTV was associated with an additional 2% of crimes cleared, but only significantly so for thefts. In total, they found that the introduction of 293 cameras was associated with 277 more thefts cleared, but considering that theft is a fairly low cost crime they concluded that it was dubious if the cameras were cost effective.…”
Section: Cctv and Crime Clearancementioning
confidence: 94%
See 1 more Smart Citation
“…Coupe and Kaur (2005) similarly found that clearance for burglary was significantly higher when the crime took place at a CCTV monitored location. Jung and Wheeler (2019) similarly showed that the introduction of CCTV was associated with an additional 2% of crimes cleared, but only significantly so for thefts. In total, they found that the introduction of 293 cameras was associated with 277 more thefts cleared, but considering that theft is a fairly low cost crime they concluded that it was dubious if the cameras were cost effective.…”
Section: Cctv and Crime Clearancementioning
confidence: 94%
“…The effect of CCTV on crime clearance can as suggested by Jung and Wheeler (2019) be related both to real time monitoring leading to quick apprehension of suspects, and to identifying suspects after the fact through considering recorded video. Some earlier research on CCTV in investigative work noted that the video quality at times was insufficient for it to be useful, especially at night and for residential areas (Gill & Spriggs, 2005).…”
Section: Cctv and Crime Clearancementioning
confidence: 99%
“…While this can make it difficult for staff to use cameras to actively monitor resident behavior, they are an excellent tool for retroactively investigating infractions. Studies in noncorrectional settings have also found that CCTV cameras may help improve crime clearances (Ashby, 2017; Jung & Wheeler, 2019; Morgan & Dowling, 2019), even when they do not prevent or reduce the number of crimes in their vicinity (Robin et al, 2020). Thus, while there are mixed findings about the impact of CCTV cameras on prison-based infractions and safety, this technology may improve investigations into infractions and other critical incidents.…”
Section: Correctional Safety and Securitymentioning
confidence: 99%
“…Thus, we first hypothesize that the intervention will reduce the total number of infractions . Studies in public settings have found that CCTV cameras may help improve crime clearances (Jung & Wheeler, 2019; Morgan & Dowling, 2019; Robin et al, 2020), while upgraded surveillance systems can drastically improve the clarity of video feeds and reduce blind spots (Shukla et al, 2021b). Our second hypothesis is that the intervention will increase the number of infractions that are found to have a guilty disposition .…”
Section: Current Studymentioning
confidence: 99%
“…Meningkatnya sistem pengawasan CCTV mampu menekan kasus kejahatan dan mempermudah pencarian pelaku kriminal [2]. Namun di sisi lain, pengawasan dengan CCTV bergantung penuh pada operator yang bertugas memantau dan mengawasi.…”
Section: Pendahuluanunclassified